2020
DOI: 10.1098/rspb.2020.1869
|View full text |Cite
|
Sign up to set email alerts
|

Is the X chromosome a hot spot for sexually antagonistic polymorphisms? Biases in current empirical tests of classical theory

Abstract: Females and males carry nearly identical genomes, which can constrain the evolution of sexual dimorphism and generate conditions that are favourable for maintaining sexually antagonistic (SA) polymorphisms, in which alleles beneficial for one sex are deleterious for the other. An influential theoretical prediction, by Rice (Rice 1984 Evolution 38 , 735–742), is that the X chromosome should be a ‘hot spot’ (i.e. enriched) for SA polymorphisms. While important caveats to Rice'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 84 publications
(166 reference statements)
1
48
0
Order By: Relevance
“…The total number of loci is relatively small however, which may limit power to identify such biases if they exist. We also did not find any examples of SA loci on the X-chromosome, which may or may not be a hotspot of sexual antagonism (Fry, 2010; Rice, 1984; Ruzicka and Connallon, 2020). This was expected given that it is commonly not included in genome-wide analyses (Wise et al, 2013), although most of the papers we reviewed were candidate gene studies.…”
Section: Discussionmentioning
confidence: 52%
“…The total number of loci is relatively small however, which may limit power to identify such biases if they exist. We also did not find any examples of SA loci on the X-chromosome, which may or may not be a hotspot of sexual antagonism (Fry, 2010; Rice, 1984; Ruzicka and Connallon, 2020). This was expected given that it is commonly not included in genome-wide analyses (Wise et al, 2013), although most of the papers we reviewed were candidate gene studies.…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, whilst it has been suggested that the X chromosome should be relatively enriched for sexually antagonistic polymorphisms in eumendelian systems as compared to the autosomes (Rice 1984), again this depends on assumptions about dominance (Fry 2010; Ruzicka and Connallon 2020). We find here that the same is true of comparisons between PGE and X chromosomes/arrhenotoky, with arrhenotokous organisms ones having a higher potential for polymorphism under parallel dominance, but a smaller space for polymorphisms under dominance reversals (see Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%
“…We find here that the same is true of comparisons between PGE and X chromosomes/arrhenotoky, with arrhenotokous organisms ones having a higher potential for polymorphism under parallel dominance, but a smaller space for polymorphisms under dominance reversals (see Supplementary Material). Additionally, such sexually antagonistic polymorphisms may be easier to detect in some haplodiploid species as compared to eumendelian ones, because the asymmetric transmission genetics means that allele frequency differences that build up between the sexes in one generation, will carry over to the next (Crow and Kimura 1970; Ruzicka and Connallon 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2007 ; Lucotte et al. 2016 ) (but see Ruzicka and Connallon 2020 ). SA selection can lead to the evolution of sex‐biased gene expression (Connallon and Clark 2010 ), leading to sexual dimorphism (Lande 1980 ).…”
Section: Introductionmentioning
confidence: 98%